Path modeling and geospatial analysis of ESG implementation among forest-based SMES in Jayapura - Pangayow, Bill; Safkaur, Otniel; Matani, Cornelia; Karoma, Yulianti; Salle, Hesti; Mudassir, Annisa Fitriah; Pedroso, Maybelyn (Journal of Accounting and Investment, 2026)
Research aims: This study examines the effect of Ownership Commitment (OC) on Environmental, Social, and Governance (ESG) implementation among forest-based SMEs in Jayapura by testing the moderating roles of Stakeholder Expectation (SE) and Regulation Threat (RT), while mapping the spatial distribution of ESG performance.Design/Methodology/Approach: A quantitative, explanatory, cross-sectional design was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with WarpPLS. Primary data were collected through structured questionnaires from 58 forest-based SMEs in Jayapura City and Regency. GPS Map Camera was used to capture firm coordinates, and spatial analysis was conducted in R using the sf and leaflet packages.Research findings: Ownership Commitment significantly enhances ESG implementation. Regulation Threat positively moderates the OC–ESG relationship, whereas Stakeholder Expectation weakens it. The model explains 24% of the variance in ESG implementation. Spatial analysis identifies higher ESG performance along the Abepura–Waena–Sentani corridor, while semi-peripheral and coastal areas such as Holtekamp, Koya Barat, and Koya Timur exhibit relatively lower performance.Theoretical contribution/Originality: The study integrates stewardship, institutional, and stakeholder theories within a spatially informed framework by combining PLS-SEM with geospatial analysis.Practitioner/Policy implication: Findings support location-specific ESG policies, stronger ownership commitment, and balanced regulatory and stakeholder interventions.Research limitations/Implications: Limitations include the cross-sectional design, region-specific sample, and reliance on self-reported ESG measures.